Leaders and Employees’ Perspectives on Participative Management as an Empowerment Strategy to Improve University Employee Performance In Indonesia - Burhanuddin, Burhanuddin; Aspland, Tania; Darmawan, I Gusti Ngurah; Ben, Francisco (International Research-Based Education Journal, 2023)
This study examined participative management as one of the empowerment strategies to improve employee performance including commitment, attendance rate, and quality of customer services. This study was conducted to examine how participative management as a strategy influence university staff performance, and how employees and their unit leaders regard this relation. It involved leaders of the units and employees within the specified university structure in Indonesia. Results show that participative management is related with the increased employee performance, but this finding is perceived differently by university head leaders and their subordinates. The empowerment strategy enhanced staff performance through promoting positive work attitudes in terms job satisfaction, self-autonomy, tasks meaningfulness, and security. Differing positions influenced perceptions on those effects. Future studies are necessary focussing on other elements to pursue broader insights about the impacts of participative management system on performance.